2011
DOI: 10.1063/1.3660697
|View full text |Cite
|
Sign up to set email alerts
|

Interface trap density metrology from sub-threshold transport in highly scaled undoped Si n-FinFETs

Abstract: Channel conductance measurements can be used as a tool to study thermally activated electron transport in the sub-threshold region of state-of-art FinFETs. Together with theoretical TightBinding (TB) calculations, this technique can be used to understand the evolution of source-tochannel barrier height (E b ) and of active channel area (S) with gate bias (Vgs). The quantitative difference between experimental and theoretical values that we observe can be attributed to the interface traps present in these FinFE… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…However, it needs to be pointed out that Equation further requires a negligible density of deep trap states in the bulk material, a condition that in our case likely is not well fulfilled, given the fact that an electrically active material is diffusing into the semiconductor film. It is well known that the subthreshold regime depends on both deep interface trap states and deep bulk trap states so that N trap as calculated above contains contributions from bulk trap states which in turn is likely the reason for the fluctuations of these numbers, e.g., in the case of N2200 (Table S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…However, it needs to be pointed out that Equation further requires a negligible density of deep trap states in the bulk material, a condition that in our case likely is not well fulfilled, given the fact that an electrically active material is diffusing into the semiconductor film. It is well known that the subthreshold regime depends on both deep interface trap states and deep bulk trap states so that N trap as calculated above contains contributions from bulk trap states which in turn is likely the reason for the fluctuations of these numbers, e.g., in the case of N2200 (Table S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The effect of silicon crystal orientation on effective mass is also theoretically calculated and put forth by them. Paul et al has demonstrated variation in E c with change in thickness of Si material [69]. They have even demonstrated variation in E c with change in orientation of Si crystal.…”
Section: Introductionmentioning
confidence: 97%
“…Except planar MOSFETs, fin-type field effect transistors (FinFETs) with HKMG play a key role in sub-22-nm technology nodes to boost electrical performance [ 14 - 16 ] and suppress various fluctuations. Recent studies reported the density of interface traps ( D it ) resulting from the orientations of the vertical fin channel of FinFETs [ 6 , 17 ]. The effects of RITs on sub-22-nm FinFETs have also been reported and compared between different device structures [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%